Retroform Cervical Dystonia: Target Muscle Selection and Efficacy of Botulinum Toxin Injection - Hu, Yaowen; Pan, Lizhen; Su, Junhui; Chen, Shuzhen; Zhang, Xiaolong; Pan, Yougui; Jin, Lingjing; Teng, Fei (Frontiers in Neurology, 2022)
Introduction: Retroform cervical dystonia (RCD) which includes retrocaput and retrocollis is a rare form of cervical dystonia. Few reports have been published on RCD. The present study aimed to characterize the target muscles involved in RCD and the efficacy of botulinum toxin type A (BTX-A) injection. Methods: Consecutive cervical dystonia patients over a 10-year period with RCD as the most problematic feature were retrospectively analyzed. Target muscles were screened and confirmed based on clinical evaluation, single-photon emission computed tomography and electromyography. In addition, efficacy and adverse events following BTX-A injection in RCD patients were evaluated. Results: A total of 34 RCD patients were included, 18 of whom presented as retrocaput and 16 as retrocollis. The most frequently injected muscles in RCD were splenius capitis (SPCa, 97.1%) and semispinalis capitis (SSCa, 97.1%), followed by levator scapulae (LS, 50.0%), rectus capitis posterior major (RCPM, 47.1%), trapezius (TPZ, 41.2%), and sternocleidomastoid muscle (SCM, 41.2%). Besides cervical muscles, erector spinae was also injected in 17.6% of patients. Most muscles were predominantly bilaterally injected. The injection schemes of retrocaput and retrocollis were similar, possibly due to the fact that patients with retrocollis often combined with retrocaput. BTX-A injection achieved satisfactory therapeutic effect in RCD, with an average symptom relief rate of 69.0% ± 16.7%. Mild dysphagia (17.6%) and posterior cervical muscle weakness (17.6%) were the most common adverse events. Conclusion: SPCa, SSCa, LS, RCPM, LS and SCM were commonly and often bilaterally injected in RCD. RCD patients could achieve satisfactory symptom relief after BTX-A injection.